Pediatric Asthma: A Global Epidemic - Denise Serebrisky (Ubiquity Press, 2019)
The global prevalence, morbidity and mortality related to childhood asthma among children has increased significantly over the last 40 years. Although asthma is recognized as the most common chronic disease in children, issues of underdiagnosis and undertreatment persist. There are substantial global variations in the prevalence of asthma symptoms in children, with up to 13-fold differences between countries. The rising number of hospital admissions for asthma may reflect an increase in asthma severity, poor disease management and/or the effect of poverty. The financial burden of asthma is relatively high within developed countries (those for which data is available) spending 1 to 2% of their healthcare budget on this condition. Established in 1989, the Global Initiative for Asthma (GINA) attempts to raise awareness about the increasing prevalence of asthma, improve management and reduce the burden of asthma worldwide. Despite global efforts, GINA has not achieved its goal, even among developed nations. There are multiple barriers to reducing the global burden of asthma, including limited access to care and/or medications, and lack of prioritization as a public healthcare priority. In addition, the diversity of healthcare systems worldwide and large differences in access to care require that asthma management guidelines be tailored to local needs.